Answer:
![9x + x - 4x = 6x](https://tex.z-dn.net/?f=9x%20%2B%20x%20-%204x%20%3D%206x)
they're all like terms so we just add and subtract
The greatest common factor is ![12xy](https://tex.z-dn.net/?f=12xy)
Explanation:
The given expression is ![12xy^6+60xy](https://tex.z-dn.net/?f=12xy%5E6%2B60xy)
We need to determine the greatest common factor of the given expression.
The greatest common factor of two numbers is the largest number of the two numbers that divides them both.
Hence, from the given expression, let us common out the highest factor that divides the two numbers.
Thus, we have,
![12xy^6+60xy=12xy(y^5+5y)](https://tex.z-dn.net/?f=12xy%5E6%2B60xy%3D12xy%28y%5E5%2B5y%29)
Thus, the largest number that divides both the terms is ![12xy](https://tex.z-dn.net/?f=12xy)
Hence, the greatest common factor of the given expression is ![12xy](https://tex.z-dn.net/?f=12xy)
![(4x^2 - x + 6) - (x^2 + 3) = 4x^2 - x + 6 - x^2 - 3 = 3x^2 - x + 3](https://tex.z-dn.net/?f=%284x%5E2%20-%20x%20%2B%206%29%20-%20%28x%5E2%20%2B%203%29%20%3D%204x%5E2%20-%20x%20%2B%206%20-%20x%5E2%20-%203%20%3D%203x%5E2%20-%20x%20%2B%203)
-----------------------------------------------
Answer: 3x² - x + 3 (Answer D)-----------------------------------------------